Dampak Penurunan Tarif di Skema Request-Offer Taiwan dan Indonesia terhadap Ekonomi Makro Indonesia: Simulasi GTAP Versi 9 - Betrix Silitonga (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Cooperation between Taiwan and Indonesia continues and develops in various fields. Taiwan is Indonesia's main trading partner. This research to analyze the impact of Taiwan dan Indonesia cooperation through tariff reductions with pessimistic scenarios (tariff reductions of 50%) and optimistic scenarios (tariff reductions of 95%) on commodities contained in request-offer schemes that are applied reciprocallously in each country (Taiwan and Indonesia). Both scenarios are applied to analyze their impact on Indonesia's macroeconomy which includes welfare, Gross Domestic Product (GDP), government and private consumption, investment, government spending, trade balance, and inflation. The analysis method used is the simulation of Global Trade Analysis Project (GTAP) versi 9 database. Indonesia's welfare, consumption (government and private), investment, government spending, and inflation increased in both tariff reduction scenarios, while Indonesia's trade balance declined in both tariff reduction scenarios. Indonesia needs to increase competitiveness of commodities contained and added value in the Taiwan and Indonesia request-offer schemes to increase the capacity and quality of Indonesia's exports in Taiwan.